Prolonged drug delivery system of an antifungal drug by association with polyamidoamine dendrimers - Jose, Jobin (Int J Pharm Investig, 2016)
INTRODUCTION: The potent antifungal agent amphotericin B (AmB) is not freely soluble in water. The clinical use of AmB is limited by nephrotoxicity and poor water solubility. Polyamidoamine (PAMAM) dendrimer offers an identical carrier for drug binding that has the capacity to attach and discharge drugs in numerous ways. MATERIALS AND METHODS: In this research work, we explored the potential of PAMAM dendrimers to improve the solubility of AmB. RESULTS AND DISCUSSION: The experimental results indicated that the solubility of AmB was greatly enhanced in the presence of PAMAM dendrimer solutions. Results indicated that the solubility of AmB enhanced with increase in dendrimer generations as well as concentration. In vitro release studies of AmB in the presence of the third generation of PAMAM dendrimers was performed by the dialysis method. Our research work revealed that binding of drug into dendrimers led to sustained release of AmB in vitro. CONCLUSION: Based on the stability studies, it was concluded that the drug dendrimer complex should be stored in a dark place at a cool temperature.